The Role Of Hydroxyapatite Materials On Collagen Synthesis In Alveolar Bone Defects Healing - Yosefin Adventa; Nanik Zubaidah (Conservative Dentistry Journal, 2021)
Background: There are several cases in dentistry that cause alveolar bone defects, including periodontal disease, major trauma after tooth extraction, post-cyst enucleation, and post-surgery. Healing of alveolar bone defects can be treated in the form of bone grafting to restore the function and structure of damaged bone tissue. Hydroxyapatite has been proven to have some good properties such as biocompatible, bioactive, and osteoconductive. Osteoconductive materials serve as scaffold for osteoblasts to attach, grow, and differentiate to form new bone. Osteoblasts will synthesize collagen type 1 which functions to mineralize the bone matrix. Objective: To explain the role of hydroxyapatite on collagen synthesis in alveolar bone defects healing. Reviews: In this review article discusses the healing process of alveolar bone defects, the characteristics of the hydroxyapatite material, collagen synthesis and also 4 kinds of natural substances that can be used as a source of hydroxyapatite material for supporting the bone healing process. These natural materials include bovine bones, egg shells, crab shells, and calcite rocks. Conclusion: Hydroxyapatite material has a role in collagen synthesis in the healing process of alveolar bone defects.